El capital humano y los retornos a la educación en Ecuador (Estudios) - Tarupi Montenegro, Edisson (2017)
This paper analyzes the returns to education in Ecuador where the labor market recognizes the level of education in employees and therefore requires setting wage variations due to education and levels, finding that returns to secondary education fall while higher education show a growing trend. General indicators of the variation in wages that identify trends by region and gender are also presented.